KEDUDUKAN HUKUM HARTA BERSAMA PASCA PUTUSNYAPERKAWINAN - Rosalinda Mulyadi (2022)
Dissolution of marriage is divided into two, namely divorce and death. The dissolution of the marriage raises another problem in the form of joint property of husband and wife. Property acquired after marriage is called joint property. The Regulation Law Number 16 of 2019 Juncto Law Number 1 of 1974 article 37 concerning the Principles of Marriage, Constraints in the position of joint property after the termination of marriage, there is no regulation for joint property in mixed marriages of different nationalities and mixed marriages of different beliefs. The method are juridical and normative, based on library and statutory data and case studies with register number 1048 PK/Pdt/2019, namely the dissolution of marriage due to divorce of different nationalities (divorce) and the case with register number 16K/AG/2010 the termination marriage of different religion due to death (divorce). literature study using books, journals, dictionaries, laws, news and other scientific articles, this research uses the theory of justice.The research of the comparison in this case is the lack of laws governing joint property in mixed marriages which is the strongest evidence is a marriage certificate. based on justice according to John Rawls' theory Justice must be able to protect the weak with legal protection and legal certainty so that it must be created according to Aristotle's theory that justice can be achieved by complying with the law but must have good legal regulations so that the Court's Decision is fair as said Thomas Hoebes. The conclusion regarding the position of joint property after the termination of the marriage because it uses the regulation of lawnumber 16 of 2019 in juncto law number 1 of 1974 concerning marriage and the Civil Code then the reasons for the judge's consideration based on the decision to include the judge's decision in the case. Keywords: Divorce, Joint property, Transnational marriage